Photoconductivity relaxation processes in Cu1−xZnxInS2 solid solutions. (November 2015) - Bozhko, V.V.; Novosad, A.V.; Parasyuk, O.V.; Vainorius, N.; Vertelis, V.; Nekrošius, A.; Kažukauskas, V.
Abstract: Photoconductivity and its relaxation in Cu1− x Zn x In2 S4 alloys ( x =0–16) single crystals were investigated in the temperature range 30–100 K. The long-lasting relaxation processes ( τ ~10 3  s) and induced photoconductivity phenomena were identified. The main parameters characterizing the photoconductivity kinetic were determined. The observed phenomena were analyzed by taking into account effects of the trapping levels. It is shown that relaxation of the photoconductivity and induced photoconductivity are controlled by the multicenter recombination in which both 'fast' and 'slow' recombination centers take part.